Pengaruh Penambahan Agar-agar Terhadap Sifat Sensori Minuman Jeli Gandaria (Bouea macrophylla Griff) - Breemer, Rachel; Picauly, Priscillia; Tetelepta, Gilian (Jurnal Agrosilvopasture-Tech, 2023)
Functional drinks with a semi-solid form and usually consumed using a straw to suck are known as jelly drinks. Generally, this drink is made from fruit extracted or from a mixture of water and essence with high acidity. This study was conducted with the aim of determining the appropriate agar concentration on the sensory characteristics of the gandaria jelly drink. The design used in this study is a Complete Randomized Design (RAL) with the main factor being agar concentration, which consists of 4 treatment levels as follows: AA1 = Agar Concentration 2%, AA3 = Agar-agar Concentration 4%, AA5 = Agar-agar Concentration 6% and AA7 = Agar-agar Concentration 8%. The results of the study of jelly drink gandaria with gelatinous concentration treatment produced values of color hedonic characteristics with a scale of somewhat like to like (2.5-3), taste, texture, aroma, and suction power with a scale of somewhat like with a score of each (2.4 - 2.9; 2.1 - 2.8; 2, - 2.8; 2.3 - 2.9).